Experimental and numerical study on an innovative trapezoidal-shaped damper to improve the behavior of CBF braces - Thongchom, Chanachai; Ghamari, Ali; Putra Jaya, Ramadhansyah; Benjeddoud, Omrane (MDPI, 2023)
Among the existing passive energy dampers, I-shaped shear dampers had shown suitable performance in experimental and numerical studies. Although they improve the dissipating energy and ductility of concentrically braced frames (CBFs), they reduce the stiffness and ultimate strength of the system. Three approaches are generally used to overcome the problem, including (a) increasing the thinness of the shear plates, (b) increasing the number of shear plates, and (c) using more dampers in more bays. The mentioned approaches increase construction costs. Accordingly, to overcome this shortcoming, in this paper, an innovative shear damper with a trapezoidal shape is proposed and investigated experimentally and numerically. The results indicated that when using the same material for I-shaped shear dampers and the proposed damper, the proposed damper has greater ultimate strength, elastic stiffness, and dissipating energy capacity. Additionally, the flange plates are more effective in the behavior of the proposed damper than the I-shaped damper. Moreover, required equations were proposed to design the damper.